Kinematic Analysis of the Distal Radioulnar Joint in Asymptomatic Wrists Using 4-Dimensional Computed Tomography–Motion Pattern and Interreader Reliability. Issue 3 (May 2019) - Shakoor, Delaram; Hafezi-Nejad, Nima; Haj-Mirzaian, Arya; Shores, Jaimie T.; Lifchez, Scott D.; Morelli, John N.; Thakur, Uma; Demehri, Shadpour
Abstract : Purpose: The aim of this study was to determine the normal measurement values and interobserver performance of the distal radioulnar joint during wrist pronation-supination using 4-dimensional computed tomography (CT). Methods: Four-dimensional CT examinations were performed on the asymptomatic contralateral wrists of 10 patients with unilateral chronic wrist pain. Measurements were conducted using the modified radioulnar (mRU) line and epicenter (Epi) methods. Volar subluxation of the ulnar head was demonstrated with negative values. Wilcoxon rank sum test was used to determine the measurement changes. Interobserver agreements were assessed using interclass correlation coefficients. Results: In pronation, mRU line measurements (median, 0.09; interquartile range, 0–0.15) were significantly larger than in supination (median, −0.1; interquartile range, −0.18 to 0; P = 0.008).The Epi measurements were not significantly different in pronation (median, 0.03; interquartile range, 0.01–0.07) and supination (median, 0.06; interquartile range, 0.01–0.1; P = 0.799). There was an excellent inter-observer agreement between the two readers using mRU and Epi methods in pronation (0.982, 0.898), midpoint (0.994, 0.827) and supination (0.989, 0.972) positions, respectively. Conclusions: Using 4-dimensional CT examination, distal radioulnar joint kinematics in asymptomatic wrists demonstrate excellent interobserver agreements with increased volar ulnar subluxation with supination as detected using mRU, but not the Epi method.